2007
DOI: 10.5194/bg-4-255-2007
|View full text |Cite
|
Sign up to set email alerts
|

<I>nirS</I>-containing denitrifier communities in the water column and sediment of the Baltic Sea

Abstract: Abstract. The aim of this study was to compare structural differences in the nirS-type denitrifying microbial communities along the environmental gradients observed in the water column and coastal sediments of the Baltic Sea. To link community structure and environmental gradients, denitrifier communities were analyzed by terminal restriction fragment length polymorphism (T-RFLP) based on nirS as a functional marker gene for denitrification. nirS-type denitrifier community composition was further evaluated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…This result is unexpected considering that nirSdenitrifiers have been frequently found in estuarine and marine habitats (Braker et al 2000;Liu et al 2003;Jayakumar et al 2004;Santoro et al 2006) and have been reported previously in the water column and sediments of the Baltic Sea (Brettar et al 2001;Hannig et al 2006;Falk et al 2007). Therefore, we consider the restricted number of nirS sequences obtained here to reflect the actual situation at the sampling time, but not as an indication of the absence of nirS-denitrifiers in the water column of the Baltic Sea.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…This result is unexpected considering that nirSdenitrifiers have been frequently found in estuarine and marine habitats (Braker et al 2000;Liu et al 2003;Jayakumar et al 2004;Santoro et al 2006) and have been reported previously in the water column and sediments of the Baltic Sea (Brettar et al 2001;Hannig et al 2006;Falk et al 2007). Therefore, we consider the restricted number of nirS sequences obtained here to reflect the actual situation at the sampling time, but not as an indication of the absence of nirS-denitrifiers in the water column of the Baltic Sea.…”
Section: Discussionmentioning
confidence: 45%
“…Different studies analyzing denitrifying bacterial communities in the Baltic Sea, the world's largest brackish environment, suggest relatively low diversity of nirS-denitrifying bacteria and have failed to recover nirK sequences from the water column and sediments (Brettar et al 2001;Hannig et al 2006;Falk et al 2007). However, recently a study in the suboxic zone of the water column (Oakley et al 2007) showed higher variation in nirK compared to nirS.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Bourbonnais et al (24) found low diversity and an abundance of nirS-containing bacteria in diffuse hydrothermal vent fluids that were reportedly dominated by Epsilonproteobacteria, despite finding other evidence for substantial denitrification (44,45). Similar discrepancies between rate measurements (54)(55)(56) and nirS gene studies (12,20,21) have been reported for the Baltic Sea, where Epsilonproteobacteria of the genus Sulfurimonas are prominent (57,58), yet nirS community analysis found no genes related to this group (21). In both of these locations, the dominant Epsilonproteobacteria were not recovered using standard primers for diversity assessment of nirS genes, suggesting a need for a multiple-primer approach to better understand the structural dynamics of denitrifying communities in environments that favor autotrophic denitrification.…”
Section: Discussionmentioning
confidence: 46%
“…This interest is evidenced by the numerous studies of denitrifier functional gene diversity that have been undertaken in a variety of aquatic environments, including estuarine sediments (3)(4)(5)(6)(7), freshwater systems (8)(9)(10)(11)(12), coastal marine waters and sediments (4,5,(13)(14)(15), oxygen minimum zones and anoxic basins (12,(16)(17)(18)(19)(20)(21)(22)(23), hydrothermal vents (24,25), and deep-sea sediments (26). The ability to denitrify exists across a wide breadth of bacteria and archaea (2) that may be favored under different environmental conditions.…”
mentioning
confidence: 99%